Development of Public Private Partnership in the Republic of Kazakhstan - Shynbergenov, N. (Maqsut Narikbayev University International School of Economics, 2024)
This thesis investigates the influence of various characteristics on project costs and the volume of attracted investments in Public-Private Partnerships (PPPs) in Kazakhstan. Using a comprehensive dataset compiled from numerous PPP projects within the country, the study employs Ordinary Least Squares (OLS) regression analysis to explore how factors such as project level, object type, economic sphere, and type of initiative impact the financial metrics of these projects. The quantitative analysis reveals significant findings about how these variables affect project costs and investment attraction. For instance, projects at the national level tend to have higher costs but also attract more significant investments compared to local projects, likely due to the scale of the projects and government backing, which reduces perceived investor risk. High-tech projects are shown to be more expensive, highlighting the need for specialized investment in technology-driven sectors. The analysis also points out that the economic sphere of a project has varying impacts on its ability to attract investments; projects in sectors with government guarantees, regardless of the economic sphere, tend to attract more investments. Qualitative interviews with key stakeholders—including representatives from the government, private investors, and a PPP development center—complement the quantitative findings. These interviews underscore the importance of strategic government support and the need for balanced regulatory frameworks to foster a conducive environment for PPP development. Stakeholders emphasize the necessity of adopting international best practices and adapting them to the local context to enhance the effectiveness of PPP projects in Kazakhstan. The study concludes that both the government and private sectors must collaborate more closely to leverage the full potential of PPPs. Recommendations for policy adjustments are provided, focusing on improving legal frameworks, increasing transparency, and strengthening government commitments to PPP projects. This research contributes to a deeper understanding of how different project characteristics influence the economic outcomes of PPPs and offers insights into strategic decision-making for future PPP initiatives in Kazakhstan. This thesis not only contributes to academic knowledge by filling gaps in existing research on PPPs in Kazakhstan but also offers practical recommendations that could help in refining the approaches to PPP implementation, ensuring that these projects are both cost-effective and attractive to investors, thereby facilitating sustainable economic development.
Keywords: public–private partnerships (PPPs); project costs; investment attraction; OLS regression analysis; government support; Kazakhstan